(3cJGH GdLZQGajGs - (3CMeO Hf GdMSjf GdMhGQfjs ((3eOjfI eUQ HGH GdbfWQI s)
(3ChdgG (B:s
(3GdMeO ddg SjOi GdfgYe hhdi GdMeO CeG HYO aEfi PcQJ ai cJGHi gPG Cbdje GdGQV Ydi GdeeGdc hbUOJ efgG HdGO GdESdGe s
(3BNQgG (B:s
(3hef eYHQ jO MSGf Edi OSJGb efc eQMdJGf hef OSJGb efc jYHQ fgQ HLGY Je GdcJGH HYhf Gddg s
(3GdfSNI HgG MhGTs
(3Ydjg bQGAGJ hJedcGJs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdLZQGajG h GdHdOGfs